2014
DOI: 10.1186/1472-6750-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of heterologous protein production in Chinese hamster ovary cells under overexpression of spliced form of human X-box binding protein

Abstract: BackgroundThe optimization of protein production is a complex and challenging problem in biotechnology. Different techniques for transcription, translation engineering and the optimization of cell culture conditions have been used to improve protein secretion, but there remain many open problems involving post-translational modifications of the secreted protein and cell line stability.ResultsIn this work, we focus on the regulation of secreted protein specific productivity (using a recombinant human immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Overexpression of XBP1s leads to high levels of expression of XBP1 S protein, to the expansion of the ER and an increased expression of secreted proteins 25 , 28 . Preconditioning the ER to stress by XBP1s expression could prevent IRE1α activation, thereby repressing splicing of endogenous XBP1u.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of XBP1s leads to high levels of expression of XBP1 S protein, to the expansion of the ER and an increased expression of secreted proteins 25 , 28 . Preconditioning the ER to stress by XBP1s expression could prevent IRE1α activation, thereby repressing splicing of endogenous XBP1u.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were performed as described previously [26]. Briefly, the supernatants of the co-transfected CHO-K1 cells and the control supernatants were collected after 48 h of transfection and applied to the Nunc/Maxisorp Immunoplate (Thermo Scientific, Waltham, MA, USA), which was preliminarily incubated with a 1:3000 dilution of the primary antibody [goat antihuman IgG (H ?…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Recent studies indicate that low levels of UPR activation are observed in antibody expressing CHO cells when cultured in seed train media, however, UPR is further triggered when CHO cell lines are grown in nutrient‐rich production media. Mounting a timely and rapid UPR response, in addition to overexpression of certain ER‐chaperones (specifically BiP), seems to correlate with higher antibody expression in CHO cells …”
Section: Introductionmentioning
confidence: 99%